Virus-Like Particles Are Efficient Tools for Boosting mRNA-Induced Antibodies - Vogt, Anne-Cathrine S.; Jörg, Lukas; Martina, Byron; Krenger, Pascal S.; Chang, Xinyue; Zeltins, Andris; Vogel, Monique; Mohsen, Mona O.; Bachmann, Martin F. (Frontiers in Immunology, 2022)
mRNA based vaccines against COVID-19 have proven most successful at keeping the SARS-CoV-2 pandemic at bay in many countries. Recently, there is an increased interest in heterologous prime-boost vaccination strategies for COVID-19 to maintain antibody responses for the control of continuously emerging SARS-CoV-2 variants of concern (VoCs) and to overcome other obstacles such as supply shortage, costs and reduced safety issues or inadequately induced immune-responses. In this study, we investigated the antibody responses induced by heterologous prime-boost with vaccines based on mRNA and virus-like particles (VLPs). The VLP-based mCuMVTT-RBM vaccine candidate and the approved mRNA-1273 vaccine were used for this purpose. We find that homologous prime boost regimens with either mRNA or VLP induced high levels of high avidity antibodies. Optimal antibody responses were, however, induced by heterologous regimens both for priming with mRNA and boosting with VLP and vice versa, priming with VLP and boosting with mRNA. Thus, heterologous prime boost strategies may be able to optimize efficacy and economics of novel vaccine strategies.